KEMAMPUAN SINTESIS SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALLY, REPETITION) DI SMA NEGERI 3 KEJURUAN MUDA - Muliati, Sri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aims to find out how the students' synthesis ability in learning mathematics through the AIR (Auditory, Intellectually, Repetition) learning model in SMA Negeri 3 Kejuruan Muda. The method used in this research is descriptive quantitative method. The population in this study were all students of class X MIA. Using a simple random sampling technique, class X MIA 1 was selected as a sample. Data collection techniques using test and interview instruments. Data analysis techniques using percentages. The results showed that the average value of the pretest was 33.16, and the average value of the percentage of students' synthesis abilities was 10.67%. While the average posttest score was 60.16, and the average value of the percentage of students' synthesis abilities was 61.33%. So it can be concluded that the synthesis ability of students in class X MIA 1 of SMA Negeri 3 Vocational Youth before using the AIR learning model is in the low category but after using the AIR learning model there is an increase.